Genome mining for fungal polyketide-diterpenoid hybrids: discovery of key terpene cyclases and multifunctional P450s for structural diversification. Issue 5 (6th December 2018) - Wang, Wei-Guang; Du, Lian-Qiong; Sheng, Shan-Ling; Li, Ao; Li, Yan-Ping; Cheng, Gui-Guang; Li, Gan-Peng; Sun, Guiling; Hu, Qiu-Fen; Matsuda, Yudai
Abstract : The biosynthesis of the fungal meroterpenoid chevalone E and its derivatives has been successfully elucidated and reconstituted. Abstract : A biosynthetic gene cluster for chevalone E (1 ) and its oxidized derivatives have been identified within the genome of the endophytic fungus Aspergillus versicolor 0312, by a mining strategy targeting a polyketide-diterpenoid hybrid molecule. The biosynthetic pathway has been successfully reconstituted in the heterologous fungus Aspergillus oryzae . Interestingly, two P450 monooxygenases, Cle2 and Cle4, were found to transform1 into seven new analogues including7 and8 that possess a unique five-membered lactone ring. Furthermore, the replacement of the terpene cyclase gene with that from another fungus led to the production of sartorypyrone D (11 ), which has a monocyclic terpenoid moiety. Finally, some of the compounds obtained in this study synergistically enhanced the cytotoxicity of doxorubicin (DOX) in breast cancer cells.